2021
DOI: 10.3390/ijms22041514
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Deficiency and Oxidative Stress: A Review of 9 Independent Human Cases and Animal Models

Abstract: Since Yachie et al. reported the first description of human heme oxygenase (HO)-1 deficiency more than 20 years ago, few additional human cases have been reported in the literature. A detailed analysis of the first human case of HO-1 deficiency revealed that HO-1 is involved in the protection of multiple tissues and organs from oxidative stress and excessive inflammatory reactions, through the release of multiple molecules with anti-oxidative stress and anti-inflammatory functions. HO-1 production is induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 56 publications
3
73
0
1
Order By: Relevance
“…The importance of HO-1 for vertebrates' physiology is demonstrated by hmox-1 deficient mice that mimic several abnormal features observed in 9 case reports of HO-1 deficient/mutant human patients [35]. In general, HO-1 deficiency is associated with reduced life span, asplenia/ spleen abnormalities, hepatomegaly, proteinuria, hemolytic anemia with paradoxical normo-or hypobilirubinemia, abnormal liver iron deposition, elevated thrombomodulin and von Willebrand factor on plasma, deleterious inflammation, and elevated levels of serum heme concentrations.…”
Section: Introductionmentioning
confidence: 74%
“…The importance of HO-1 for vertebrates' physiology is demonstrated by hmox-1 deficient mice that mimic several abnormal features observed in 9 case reports of HO-1 deficient/mutant human patients [35]. In general, HO-1 deficiency is associated with reduced life span, asplenia/ spleen abnormalities, hepatomegaly, proteinuria, hemolytic anemia with paradoxical normo-or hypobilirubinemia, abnormal liver iron deposition, elevated thrombomodulin and von Willebrand factor on plasma, deleterious inflammation, and elevated levels of serum heme concentrations.…”
Section: Introductionmentioning
confidence: 74%
“…Several in vivo studies with HO-1-deficiency have demonstrated a cytoprotective effect of HO-1 in human diseases including systemic inflammation, hemolysis, nephritis, asplenia, nephropathy, and vascular endothelial injury [ 9 , 10 ]. Results from clinical studies further confirmed that HO-1 protects cells by diminishing oxidative stress and inflammation, and maintaining mitochondrial integrity, thereby promoting cell survival [ 11 ]. Due to the manner in regulation of iron metabolism [ 12 ], HO-1 also play a role in mediating ferroptosis, a newly identified iron-dependent cell death [ 13 , 14 , 15 , 16 ].…”
Section: Heme Oxygenases (Hos) and Oxidative Stressmentioning
confidence: 96%
“…Mi-RNA-204/mi-RNA-211 attenuated vascular calcification and induced aging in a paracrine way through BMP2 [177]. On the contrary, bone marrow stromal cells expressing mi-RNA-183-5p showed a decreased ability of Hmox1 to protect from oxidative stress and excessive inflammatory reactions resulting in senescence and a reduced osteogenic differentiation [185].…”
Section: The Importance Of Mi-rna In Aging Functionmentioning
confidence: 99%